Hubungan antara Tingkat Kecemasan dengan Kualitas Tidur pada Pasien Composmentis di ruang Icu - Indah Puji Lestari, Indah Puji Lestari; Wahyu Endang Setyowati; Dwi Heppy Rochmawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Patients admitted to the Intensive Care Unit (ICU) frequently experience physiological disturbances that significantly affect their sleep quality. These disturbances are triggered by various factors, including repeated medical procedures, environmental noise, discomfort from medical devices, intensive interactions with healthcare workers, inappropriate lighting that disrupts circadian rhythms, pain, and the underlying disease process. Sleep disturbances in ICU patients may slow down the healing process, elevate blood pressure, trigger metabolic disorders, and increase the risk of serious complications such as stroke. This study aims to examine the relationship between anxiety levels and sleep quality among compos mentis patients in the ICU of Sultan Agung Islamic Hospital, Semarang. The research employed a correlational design with a cross-sectional method. A total of 30 respondents were included based on specific criteria. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS), while sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using the Chi-Square test to determine the relationship between the two variables. The findings showed that the distribution of male and female respondents was balanced (15 respondents each). The most common medical diagnosis was post-laparotomy (10 respondents), with the dominant age category being late elderly (10 respondents). Anxiety levels were predominantly in the moderate category (18 respondents), while the majority of respondents demonstrated poor sleep quality (17 respondents). Statistical analysis revealed a p-value of 0.001, indicating a significant relationship between anxiety levels and sleep quality. In conclusion, the study highlights that higher levels of anxiety are associated with poorer sleep quality among compos mentis patients in the ICU. These findings emphasize the importance of nursing interventions aimed at reducing anxiety to improve patient sleep quality and support recovery.